Branchial muscles of a Hill-stream Cyprinid fish Neolissochilus hexagonolepis (McClelland,1839) (Our Nature, 2018)
Different branchial muscles associated with the gill arches and gill filaments in a hill-stream cyprinid fish Neolissochilus hexagonolepis have been studied. The main branchial muscles observed are the constrictors branchiales, levatores arcuum branchialium epiarcualia obliqui, epiarcualia recti, subarcualia obliqui, subarcualia recti and subarcualia transversi. In the general plan the branchial muscles of N. hexagonolepis show similarity with those of other cyprinid fishes. However, the fish bears three pairs of coracobranchiales, common to cyprinid fishes.